Deciphering the functional roles of PE18 and PPE26 proteins in modulating Mycobacterium tuberculosis pathogenesis and immune response - Ehtram, Aquib; Shariq, Mohd; Quadir, Neha; Jamal, Salma; Pichipalli, Manjunath; Zarin, Sheeba; Sheikh, Javaid Ahmad; Ehtesham, Nasreen Z.; Hasnain, Seyed E. (Frontiers in Immunology, 2025)
IntroductionTuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a leading cause of mortality worldwide. A crucial factor in Mtb's virulence is the ESX-5 secretion system, which transports PE/PPE proteins such as PE18 and PPE26. These proteins modulate host-pathogen interactions, immune responses, and intracellular survival mechanisms. Despite their importance, the roles and molecular interactions of PE18 and PPE26 in Mtb pathogenesis require further investigation.MethodsWe explored the roles of PE18 and PPE26 using recombinant Mycobacterium smegmatis (Msmeg) as a model organism. Protein-protein interactions were analyzed biochemically to identify partners within the ESX-5 secretion system, including EspG5 and other PE/PPE proteins. Subcellular localization of these proteins was assessed via cell fractionation studies. Functional assays, including in vitro cytokine production and antigen presentation studies, were performed using TLR2/Myd88 knockout and wild-type macrophages. In vivo experiments were conducted to assess effector T-cell activation and intracellular survival. Mechanistic insights into endosome-phagosome maturation and actin cytoskeleton dynamics were obtained through fluorescence microscopy.ResultsOur biochemical analyses confirmed interactions between PE18/PPE26, PE18/PPE27, PE19/PPE25, and EspG5/PPE, highlighting their involvement in ESX-5-mediated secretion. Cell fractionation studies revealed that PE/PPE proteins predominantly localize to the cell wall, with PE18 also secreted extracellularly. In vitro and in vivo experiments demonstrated that PE18 and PPE26 activate cytokine production and antigen presentation via TLR2/Myd88-dependent signaling pathways, inducing robust effector memory T-cell responses. Recombinant Msmeg expressing PE18, PPE26, or their combination exhibited enhanced intracellular survival by disrupting endosome-phagosome maturation, likely through interference with actin cytoskeletal organization.DiscussionOur findings elucidate the pivotal roles of PE18 and PPE26 in Mtb pathogenesis, emphasizing their contributions to immune modulation and intracellular persistence. The observed disruption of actin dynamics and endosome-phagosome maturation underscores a novel mechanism by which Mtb evades host defenses. The ability of PE18 and PPE26 to induce effector T-cell responses highlights their potential as targets for host-directed therapies or vaccine development against TB. Further studies focusing on their structure-function relationships and interactions with host proteins could accelerate the development of innovative therapeutic strategies.